Close‐knit ties through thick and thin: Sharing social exclusion and acceptance enhances social bond. (26th January 2021) - Gao, Cong; Wang, Deming; Miao, Xiao‐Yan; Wang, Zuo‐Jun; Qin Chan, Kai
Abstract: Three experiments investigated whether and why sharing experiences of social exclusion or social acceptance with others strengthens social bonds. Participants experienced either social exclusion or social acceptance alongside another co‐participant who either also experienced the same outcome, or experienced a different outcome, as them. Multilevel modeling results showed that participant dyads who shared the experience of social exclusion or social acceptance felt closer to each other than those who experienced different outcomes, and that perceived similarity mediated the effect of shared experiences on social bonds. Interestingly, participants felt closer to one another after having shared social acceptance, more so than when they have shared social exclusion. Implications of the present findings are interpreted in light of theories of social exclusion, shared experiences, and social bonding.